Review:Studi Tumbuhan Sebagai Antitukak Pada Bagian Daun - Anandika, I Bagus Duta; Habibur Umami Amrullah (Program Studi Akuntansi IKOPIN, 2022)
Peptic ulcer is a collection of diseases characterized by disturbances in the mucosa of the esophagus, stomach or small intestine. The main causes of peptic ulcers are increased acid secretion and balance disturbances caused by the aggression of mucosal resistance. However, these drugs have quite severe side effects. Plants can be used as an alternative anti-ulcer treatment. This article aims to provide information on various plants that have anti-ulcer activity that have been tested on animal models. Some of these plants include Averrhoa blimbi L., Gynura pseudochina L., Phyllantus niruri L., Andrographis paniculata, and Olea europaea. Based on their activity, plants containing chemical alkaloids, terpenes, terpenoids, flavonoids, saponins, phenolic acids and tannins have been shown to have anti-ulcer effects with various effective doses.